2016
DOI: 10.1530/rep-15-0338
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 lysine 27 trimethylation acts as an epigenetic barrier in porcine nuclear reprogramming

Abstract: Aberrant epigenetic reprogramming is the main obstacle to the development of somatic cell nuclear transfer (SCNT) embryos and the generation of induced pluripotent stem (iPS) cells, which results in the low reprogramming efficiencies of SCNT and iPS. Histone H3 lysine 27 trimethylation (H3K27me3), as a repressive epigenetic mark, plays important roles in mammalian development and iPS induction. However, the reprogramming of H3K27me3 in pig remains elusive. In this study, we showed that H3K27me3 levels in porci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 32 publications
4
53
0
Order By: Relevance
“…Our scRNA-seq transcriptome also demonstrated that ZGArelated genes failed to be properly activated in MERVL À SCNT compared with normal fertilization embryos. Furthermore, a high H3K27me3 level is detrimental to bovine SCNT embryonic development, consistent with porcine SCNT reprogramming [52]. Collectively, these results suggested that SCNT embryos are H3K27me3-defective at the ZGA stage, which serves as another barrier to murine, bovine, and porcine SCNT reprogramming.…”
Section: Discussionsupporting
confidence: 57%
“…Our scRNA-seq transcriptome also demonstrated that ZGArelated genes failed to be properly activated in MERVL À SCNT compared with normal fertilization embryos. Furthermore, a high H3K27me3 level is detrimental to bovine SCNT embryonic development, consistent with porcine SCNT reprogramming [52]. Collectively, these results suggested that SCNT embryos are H3K27me3-defective at the ZGA stage, which serves as another barrier to murine, bovine, and porcine SCNT reprogramming.…”
Section: Discussionsupporting
confidence: 57%
“…5,[10][11][12] Histone H3 lysine 27 trimethylation (H3K27me3) [13][14][15] and 5-methylcytosine (5-mC), 16,17 both of which are repressive markers, have also been revealed as an obstacle for SCNT reprogramming in mammals. Previous studies have shown that the persistence of histone H3 lysine 9 trimethylation (H3K9me3) in SCNT embryos is an important barrier for nuclear reprogramming, which is responsible for abnormal embryonic genome activation (EGA), and that ectopic expression of H3K9me3 demethylase can restore the EGA defects and significantly improve the cloning efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these factors, starting with Ascl1, followed by Neurog1 and NeuroD1, have been shown to indicate neuronal specification in the epithelium, as in the central nervous system (CNS) (Chen et al, 2014; Goldstein et al, 2015; Huard et al, 1998; Jang et al, 2003; Joiner et al, 2015; Krolewski et al, 2012; Leung et al, 2007; Manglapus et al, 2004; Packard et al, 2011a, 2016; Shaker et al, 2012; Xie et al, 2016). These neurogenic factors act in opposition to drivers of non-neuronal cell differentiation such as Hes1, which directs the formation of Sus cells(Cau et al, 1997; Guillemot and Joyner, 1993; Krolewski et al, 2012; Packard et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%